Quantum dot ink composite material and preparation method thereof

The quantum dot ink composite material addresses dispersion and stability issues through a nonionic/anionic surfactant system and waterborne polyurethane, ensuring uniform films and enhanced luminescence efficiency in high-precision printing applications.

CN119220126APending Publication Date: 2024-12-31GUANGDONG ODIMING OPTOELECTRONICS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411510602.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing quantum dot ink materials suffer from issues of uneven dispersion, poor stability, and low light conversion efficiency, which affect the uniformity and thickness of film-forming layers, thereby impacting luminescent performance and efficiency in high-precision printing applications.

Method used

A quantum dot ink composite material composed of specific ratios of dispersant, solvent, surfactants, viscosity modifier, and defoamer, utilizing a nonionic/anionic surfactant compound system to form mixed micelles and double electric layers for improved dispersibility and stability, along with waterborne polyurethane for enhanced dispersion and a viscosity modifier for stability.

Benefits of technology

The composite material achieves high dispersibility and stability, enabling the formation of dense and uniform quantum dot films, enhancing optical properties and meeting the needs of high-precision printing with improved luminescence efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of quantum dot luminescent materials, and particularly relates to a quantum dot ink composite material and a preparation method thereof. The quantum dot ink composite material comprises the following components in parts by mass: 1-20 parts of a dispersing agent, 1-30 parts of a quantum dot material, 20-95 parts of a solvent, 1-10 parts of a surfactant, 0.5-10 parts of a viscosity modifier, 0.5-10 parts of a drier and 0.01-0.1 part of a defoaming agent, the surfactant is composed of a nonionic surfactant and an anionic surfactant in a ratio of 1: (1-3). The preparation method comprises the following steps: mixing a quantum dot material with a dispersant to form a uniform quantum dot dispersion liquid, adding a surfactant to further enhance dispersibility and stability, adding a viscosity modifier and a drier, and finely filtering to remove quantum dot aggregates to obtain the quantum dot ink composite material. The quantum dot ink composite material has excellent dispersity and stability, a printed quantum dot film is uniform and compact, and the printing process has good uniformity and repeatability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of quantum dot luminescent materials, and in particular to a quantum dot ink composite material and a preparation method thereof. Background Art

[0002] Quantum dots are nanoscale semiconductors that have the property of confining electrons and electron holes. Applying a certain electric field or light pressure to quantum dots can make them emit light of a specific frequency. The frequency of the emitted light changes with the size of the quantum dots. By adjusting the size of the quantum dots, the color of the light they emit can be controlled. Quantum dot materials are considered to have broad application prospects in the fields of biology, semiconductors, and tumor treatment due to their excellent optical properties, such as high color purity and tunable emission wavelength.

[0003] In the display field, quantum dot materials are used to manufacture high-resolution displays such as OLED, QLED, and liquid crystal, but the traditional production process of extruding quantum dot films will cause high temperatures, which will seriously affect the efficiency and life of quantum dots, thereby increasing the cost of using quantum dot products and reducing material utilization. At present, quantum dot ink materials have become a favorable solution to the above problems. The quantum dot ink materials are layered and coated on the surface of the diffusion plate by printing, which can avoid the high temperature of the traditional process and thus achieve the best use effect of quantum dot products.

[0004] In terms of quantum dot material performance, quantum efficiency, half-width and stability are three important indicators of quantum dot material performance. The stability of quantum dot materials has always been a focus of extensive research, and ink materials are no exception. CN113583512A discloses an ink, a quantum dot film and a quantum dot light-emitting diode, which can improve the luminous efficiency of quantum dots, but the patent does not elaborate on the stability problem of quantum dot ink. CN111378323A discloses another ink, a quantum dot film and a quantum dot light-emitting diode, which improves the film-forming property and luminescent performance of quantum dot ink, and does not study the stability and dispersibility of quantum dot ink. However, the problems of uneven dispersion and poor stability of quantum dot ink materials will make it difficult to control the uniformity and thickness of the film-forming layer, which will in turn affect the luminescent performance and light conversion efficiency. Therefore, it is necessary to develop a quantum dot ink material with good dispersibility, high stability, strong adhesion and good light conversion efficiency. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a quantum dot ink material with good dispersibility, high stability and good light conversion efficiency, which can meet the needs of high-precision printing.

[0006] On one hand, the present invention provides a quantum dot ink composite material, wherein the quantum dot ink material is composed of the following components, calculated by weight: 3 to 5 parts of a dispersant, 3 to 5 parts of a quantum dot material, 30 to 50 parts of a solvent, 0.3 to 0.5 parts of a surfactant, 0.5 to 1 parts of a viscosity modifier, 0.3 to 0.5 parts of a drying agent, and 0.03 to 0.05 parts of a defoaming agent;

[0007] The mass ratio of the nonionic surfactant to the anionic surfactant is 1:1-3.

[0008] The present invention provides a nonionic / anionic surfactant compound system. The nonionic surfactant and the anionic surfactant are compounded to form mixed micelles, which form hydrogen bonds or van der Waals forces with the surface of quantum dot particles to achieve dispersion of quantum dot materials. The nonionic surfactant and the anionic surfactant form hydrogen bonds with water molecules on the surface of the quantum dots, thereby forming a hydration layer, which can reduce the interaction force between quantum dot particles and can also make the particles that have been adsorbed with negative charges slide and stagger when approaching each other according to the steric hindrance effect.

[0009] In addition, the anionic surfactant in the surfactant compound system used in the present invention also promotes the dispersibility and stability of quantum dots in the dispersant through the principle of double electric layer. First, the anionic surfactant is ionized into anions in water and adsorbed on the surface of the quantum dots to form surface ions, and then adsorbs the counterions with opposite charges in the medium through electrostatic action. A part of the counterions is tightly combined with the particles and the surface ions to form bound counterions, and the other part of the counterions is surrounded by them to become free counterions, so that a double electric layer is formed between the surface ions and the counterions, which prevents the adsorption or aggregation between the quantum dots, reduces the formation of large particles, and then can improve the stability of the quantum dot material in the dispersant, and reduce the stratification of the quantum dot dispersion system or the sedimentation of the quantum dot aggregates.

[0010] Preferably, the nonionic surfactant is selected from polyethylene glycol, and the anionic surfactant is selected from ethylene oxide phosphate ester. The polyethylene glycol / ethylene oxide phosphate ester compound system used in the present invention has a synergistic effect.

[0011] Preferably, the dispersant is waterborne polyurethane. The dispersant used in the present invention is waterborne polyurethane, which can fully dissolve quantum dot materials. Quantum dots can only show their special properties when the particles are well dispersed, but quantum dots are nanoparticles with high specific surface energy and are in a thermodynamically unstable state. They are very easy to agglomerate to form large particles, which causes quantum dots to fail. The long-chain high molecular polymer in the waterborne polyurethane has good dispersibility to the quantum dot material through a steric stabilization mechanism, while not changing the charge distribution on the surface of the quantum dots. Waterborne polyurethane is a uniform emulsion formed by dispersing polyurethane in water, which has the advantages of non-flammable, low odor, no pollution, energy saving, and easy operation and processing. Adding a compounded surfactant on this basis can further increase the uniformity and stability of quantum dots in the dispersant.

[0012] The quantum dots are perovskite quantum dots.

[0013] Preferably, the quantum dot material is selected from one of CsPbBr3, FAPbBr3, CsPbI3 or CsPbCl3.

[0014] Preferably, the solvent is composed of water and epoxy resin in a ratio of 1:1 to 5, and the epoxy resin is bisphenol A epoxy resin.

[0015] Preferably, the viscosity modifier is selected from a mixture of hydroxyethyl cellulose ether and high boiling point kerosene in a mass ratio of 1 to 3: 1 to 2. The viscosity modifier used in the present invention is a mixture of hydroxyethyl cellulose ether and high boiling point kerosene in a mass ratio of 1 to 3: 1 to 2. Viscosity is extremely important for the stability of the dispersion system. The ratio of the viscosity modifier hydroxyethyl cellulose ether and high boiling point kerosene used in the present invention can well promote the stability of quantum dots in the dispersion system.

[0016] Preferably, the drying agent is cobalt drying oil. The present invention uses cobalt drying oil as a drying agent, which helps the quantum dot ink composite material to dry quickly after printing.

[0017] Preferably, the defoamer is fatty alcohol ethoxysiloxane. The present invention uses fatty alcohol ethoxysiloxane as a defoamer, which helps to reduce the generation of foam during the production and / or printing of quantum dot ink.

[0018] Another aspect of the present invention provides a method for preparing the quantum dot ink composite material, comprising the following steps:

[0019] S1, dissolving the quantum dot material in a solvent and mixing them evenly to obtain a quantum dot solution;

[0020] S2, mixing the quantum dot solution described in S1 with a dispersant, and mixing them evenly to form a quantum dot dispersion;

[0021] S3, adding a surfactant to the quantum dot dispersion described in S2, mixing evenly, to obtain a preliminary quantum dot ink composite material;

[0022] S4, adding a viscosity modifier and a drying agent to the quantum dot ink composite material described in S3, mixing them evenly, to obtain a quantum dot ink composite material;

[0023] S5. Finely filter the ink described in S4 to remove undispersed quantum dot aggregates to obtain a quantum dot ink composite material.

[0024] First, the quantum dot material is dissolved in a solvent, and then a dispersant is added to promote its dispersion, and then a surfactant is added to further increase the dispersibility and stability of the quantum dot material, and then a viscosity modifier is added to adjust its viscosity, and finally a drying agent is added. The quantum dot material can be fully dispersed in the quantum dot ink system used in the present invention. Finally, the aggregated quantum dot material is filtered to remove to ensure that the quantum dot ink composite material has good uniformity during use.

[0025] Preferably, the mixing methods in steps S1 to S4 are all mechanical stirring or ultrasonic dispersion, and the fine filtration in S5 is filtering using a 200-mesh screen.

[0026] The present invention has the following beneficial effects:

[0027] 1) The present invention provides a quantum dot ink composite material with high dispersibility and good stability. The surfactant compound system used can improve the dispersibility and stability of quantum dots in the dispersion system, and can enable the quantum dot ink composite material of the present invention to form a dense and uniform quantum dot film after printing, thereby meeting the needs of high-precision printing.

[0028] 2) The present invention uses water-based polyurethane as a dispersant to improve the dispersibility of the quantum dot material in the dispersion system.

[0029] 3) The viscosity modifier used in the present invention can promote the stability of quantum dots in the dispersion system.

[0030] 4) The quantum dot ink composite material provided by the present invention has good dispersibility, can significantly improve the optical properties of printed products, and has important application value and market prospects. DETAILED DESCRIPTION

[0031] The present invention is further illustrated below through the description of specific implementation methods, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of ​​the present invention, but as long as they do not deviate from the basic idea of ​​the present invention, they are all within the protection scope of the present invention.

[0032] In the following examples and comparative examples, reagents not otherwise specified are conventional reagents and can be purchased from conventional reagent production and sales companies.

[0033] Waterborne polyurethane was purchased from Hefei Huayue New Material Technology Co., Ltd., item number: D601.

[0034] Epoxy resin was purchased from Hubei Junrui Biotechnology Co., Ltd., product number: JR4612.

[0035] Quantum dot materials were purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., catalog number: 104637.

[0036] Epoxy ethylene phosphate was purchased from Shanghai Kain Chemical Co., Ltd., product number: ETERKYD 4901-B-72.

[0037] High boiling point kerosene was purchased from Shandong Xuxiang Chemical Co., Ltd., item number: 64745-95-5.

[0038] Example 1

[0039] A quantum dot ink composite material is prepared, and the specific steps are as follows:

[0040] S1. Mix water and epoxy resin in a mass ratio of 1:1 to obtain an epoxy resin aqueous solution, dissolve 5 g of quantum dot material in 50 ml of the epoxy resin aqueous solution, and perform ultrasound for 10 to 15 minutes;

[0041] S2, add 5 ml of waterborne polyurethane, mix evenly by ultrasonication for 30 to 40 minutes to form a quantum dot dispersion;

[0042] S3, add 0.5g polyethylene glycol, mix well, then add 1g ethylene oxide phosphate, mix well by ultrasonication for 10-15min;

[0043] S4, adding 0.5 g hydroxyethyl cellulose ether, 0.5 g high boiling point kerosene, 0.5 g cobalt drying oil, and 0.05 g fatty alcohol ethoxysiloxane, ultrasonically mixing for 10 min, and mixing evenly to obtain a coarse quantum dot ink;

[0044] S5. Use a 200-mesh filter to finely filter the coarse quantum dot ink described in S4 to remove undispersed quantum dot aggregates to obtain a quantum dot ink composite material.

[0045] Example 2

[0046] A quantum dot ink composite material is prepared, and the specific steps are as follows:

[0047] S1. Mix water and epoxy resin in a mass ratio of 1:2 to obtain an epoxy resin aqueous solution, dissolve 5 g of quantum dot material in 50 ml of the epoxy resin aqueous solution, and perform ultrasonication for 10 to 15 minutes;

[0048] S2, add 5 ml of waterborne polyurethane, mix evenly by ultrasonication for 30 to 40 minutes to form a quantum dot dispersion;

[0049] S3, add 0.75g polyethylene glycol, mix well, then add 0.75g ethylene oxide phosphate, mix well by ultrasonication for 10-15min;

[0050] S4, adding 0.75g hydroxyethyl cellulose ether, 0.25g high boiling point kerosene, 0.5g cobalt drying oil, and 0.05g fatty alcohol ethoxysiloxane, ultrasonically mixing for 10min, and mixing evenly to obtain a coarse quantum dot ink;

[0051] S5. Use a 200-mesh filter to finely filter the coarse quantum dot ink described in S4 to remove undispersed quantum dot aggregates to obtain a quantum dot ink composite material.

[0052] Example 3

[0053] A quantum dot ink composite material is prepared, and the specific steps are as follows:

[0054] S1. Mix water and epoxy resin in a mass ratio of 1:5 to obtain an epoxy resin aqueous solution, dissolve 5 g of quantum dot material in 50 ml of the epoxy resin aqueous solution, and perform ultrasound for 10 to 15 minutes;

[0055] S2, add 5 ml of waterborne polyurethane, mix evenly by ultrasonication for 30 to 40 minutes to form a quantum dot dispersion;

[0056] S3, add 0.375g polyethylene glycol, mix well, then add 1.125g ethylene oxide phosphate, mix well by ultrasonication for 10-15min;

[0057] S4, adding 0.33 g hydroxyethyl cellulose ether, 0.67 g high boiling point kerosene, 0.5 g cobalt drying oil, and 0.05 g fatty alcohol ethoxysiloxane, ultrasonically mixing for 10 min, and mixing evenly to obtain a coarse quantum dot ink;

[0058] S5. Use a 200-mesh filter to finely filter the coarse quantum dot ink described in S4 to remove undispersed quantum dot aggregates to obtain a quantum dot ink composite material.

[0059] Comparative Example 1

[0060] A quantum dot ink composite material is prepared, which is basically the same as Example 1, and the only difference from Example 1 is that the epoxyethylene phosphate in step S3 is replaced by dodecylamine polyoxyethylene ether.

[0061] The specific steps are as follows:

[0062] S1. Mix water and epoxy resin in a mass ratio of 1:1 to obtain an epoxy resin aqueous solution, dissolve 5 g of quantum dot material in 50 ml of the epoxy resin aqueous solution, and perform ultrasound for 10 to 15 minutes;

[0063] S2, add 5 ml of waterborne polyurethane, mix evenly by ultrasonication for 30 to 40 minutes to form a quantum dot dispersion;

[0064] S3, add 0.5g polyethylene glycol, mix well, then add 1g dodecylamine polyoxyethylene ether, and mix well by ultrasonication for 10-15min;

[0065] S4, adding 0.5 g hydroxyethyl cellulose ether, 0.5 g high boiling point kerosene, 0.5 g cobalt drying oil, and 0.05 g fatty alcohol ethoxysiloxane, ultrasonically mixing for 10 min, and mixing evenly to obtain a coarse quantum dot ink;

[0066] S5. Use a 200-mesh filter to finely filter the coarse quantum dot ink described in S4 to remove undispersed quantum dot aggregates to obtain a quantum dot ink composite material.

[0067] Comparative Example 2

[0068] A quantum dot ink composite material is prepared, which is basically the same as Example 1, and the only difference from Example 1 is that the epoxyethylene phosphate in step S3 is replaced by sodium α-olefin sulfonate.

[0069] The specific steps are as follows:

[0070] S1. Mix water and epoxy resin in a mass ratio of 1:1 to obtain an epoxy resin aqueous solution, dissolve 5 g of quantum dot material in 50 ml of the epoxy resin aqueous solution, and perform ultrasound for 10 to 15 minutes;

[0071] S2, add 5 ml of waterborne polyurethane, mix evenly by ultrasonication for 30 to 40 minutes to form a quantum dot dispersion;

[0072] S3, add 0.5g polyethylene glycol, mix well, then add 1g sodium α-olefin sulfonate, and mix well by ultrasonication for 10-15min;

[0073] S4, adding 0.5 g hydroxyethyl cellulose ether, 0.5 g high boiling point kerosene, 0.5 g cobalt drying oil, and 0.05 g fatty alcohol ethoxysiloxane, ultrasonically mixing for 10 min, and mixing evenly to obtain a coarse quantum dot ink;

[0074] S5. Use a 200-mesh filter to finely filter the coarse quantum dot ink described in S4 to remove undispersed quantum dot aggregates to obtain a quantum dot ink composite material.

[0075] Comparative Example 3

[0076] A quantum dot ink composite material was prepared, which was basically the same as Example 1, and the only difference from Example 1 was that 1.4 g of polyethylene glycol and 0.1 g of epoxy phosphate were added in step S3.

[0077] The specific steps are as follows:

[0078] S1. Mix water and epoxy resin in a mass ratio of 1:1 to obtain an epoxy resin aqueous solution, dissolve 5 g of quantum dot material in 50 ml of the epoxy resin aqueous solution, and perform ultrasound for 10 to 15 minutes;

[0079] S2, add 5 ml of waterborne polyurethane, mix evenly by ultrasonication for 30 to 40 minutes to form a quantum dot dispersion;

[0080] S3, add 1.4g polyethylene glycol, mix well, then add 0.1g ethylene oxide phosphate, mix well by ultrasonication for 10-15min;

[0081] S4, adding 0.5 g hydroxyethyl cellulose ether, 0.5 g high boiling point kerosene, 0.5 g cobalt drying oil, and 0.05 g fatty alcohol ethoxysiloxane, ultrasonically mixing for 10 min, and mixing evenly to obtain a coarse quantum dot ink;

[0082] S5. Use a 200-mesh filter to finely filter the coarse quantum dot ink described in S4 to remove undispersed quantum dot aggregates to obtain a quantum dot ink composite material.

[0083] Comparative Example 4

[0084] A quantum dot ink composite material was prepared, which was basically the same as Example 1, and the only difference from Example 1 was that 0.1 g of polyethylene glycol and 1.4 g of epoxyethylene phosphate were added in step S3.

[0085] The specific steps are as follows:

[0086] S1. Mix water and epoxy resin in a mass ratio of 1:1 to obtain an epoxy resin aqueous solution, dissolve 5 g of quantum dot material in 50 ml of the epoxy resin aqueous solution, and perform ultrasound for 10 to 15 minutes;

[0087] S2, add 5 ml of waterborne polyurethane, mix evenly by ultrasonication for 30 to 40 minutes to form a quantum dot dispersion;

[0088] S3, add 0.1g polyethylene glycol, mix well, then add 1.4g ethylene oxide phosphate, mix well by ultrasonication for 10-15min;

[0089] S4, adding 0.5 g hydroxyethyl cellulose ether, 0.5 g high boiling point kerosene, 0.5 g cobalt drying oil, and 0.05 g fatty alcohol ethoxysiloxane, ultrasonically mixing for 10 min, and mixing evenly to obtain a coarse quantum dot ink;

[0090] S5. Use a 200-mesh filter to finely filter the coarse quantum dot ink described in S4 to remove undispersed quantum dot aggregates to obtain a quantum dot ink composite material.

[0091] Comparative Example 5

[0092] A quantum dot ink composite material is prepared, which is basically the same as Example 1, and the only difference from Example 1 is that the water-based polyurethane in step S2 is replaced by an epoxy resin aqueous solution.

[0093] The specific steps are as follows:

[0094] S1. Mix water and epoxy resin in a mass ratio of 1:1 to obtain an epoxy resin aqueous solution, dissolve 5 g of quantum dot material in 50 ml of the epoxy resin aqueous solution, and perform ultrasound for 10 to 15 minutes;

[0095] S2, add 5 ml of epoxy resin aqueous solution, mix evenly by ultrasonic for 30 to 40 minutes to form a quantum dot dispersion;

[0096] S3, add 0.5g polyethylene glycol, mix well, then add 1g ethylene oxide phosphate, mix well by ultrasonication for 10-15min;

[0097] S4, adding 0.5 g hydroxyethyl cellulose ether, 0.5 g high boiling point kerosene, 0.5 g cobalt drying oil, and 0.05 g fatty alcohol ethoxysiloxane, ultrasonically mixing for 10 min, and mixing evenly to obtain a coarse quantum dot ink;

[0098] S5. Use a 200-mesh filter to finely filter the coarse quantum dot ink described in S4 to remove undispersed quantum dot aggregates to obtain a quantum dot ink composite material.

[0099] Comparative Example 6

[0100] A quantum dot ink composite material was prepared, which was basically the same as Example 1, and the only difference from Example 1 was that the high boiling point kerosene in step S4 was replaced by hydroxyethyl cellulose ether.

[0101] The specific steps are as follows:

[0102] S1. Mix water and epoxy resin in a mass ratio of 1:1 to obtain an epoxy resin aqueous solution, dissolve 5 g of quantum dot material in 50 ml of the epoxy resin aqueous solution, and perform ultrasound for 10 to 15 minutes;

[0103] S2, add 5 ml of waterborne polyurethane, mix evenly by ultrasonication for 30 to 40 minutes to form a quantum dot dispersion;

[0104] S3, add 0.5g polyethylene glycol, mix well, then add 1g ethylene oxide phosphate, mix well by ultrasonication for 10-15min;

[0105] S4, adding 1 g of hydroxyethyl cellulose ether, 0.5 g of cobalt drying oil, and 0.05 g of fatty alcohol ethoxysiloxane, ultrasonically mixing for 10 min, and mixing evenly to obtain a coarse quantum dot ink;

[0106] S5. Use a 200-mesh filter to finely filter the coarse quantum dot ink described in S4 to remove undispersed quantum dot aggregates to obtain a quantum dot ink composite material.

[0107] Comparative Example 7

[0108] A quantum dot ink composite material was prepared, which was basically the same as Example 1, and the only difference from Example 1 was that the hydroxyethyl cellulose ether in step S4 was replaced by high boiling point kerosene.

[0109] The specific steps are as follows:

[0110] S1. Mix water and epoxy resin in a mass ratio of 1:1 to obtain an epoxy resin aqueous solution, dissolve 5 g of quantum dot material in 50 ml of the epoxy resin aqueous solution, and perform ultrasound for 10 to 15 minutes;

[0111] S2, add 5 ml of waterborne polyurethane, mix evenly by ultrasonication for 30 to 40 minutes to form a quantum dot dispersion;

[0112] S3, add 0.5g polyethylene glycol, mix well, then add 1g ethylene oxide phosphate, mix well by ultrasonication for 10-15min;

[0113] S4, adding 1 g of high boiling point kerosene, 0.5 g of cobalt drying oil, and 0.05 g of fatty alcohol ethoxysiloxane, ultrasonically mixing for 10 min, and mixing evenly to obtain a coarse quantum dot ink;

[0114] S5. Use a 200-mesh filter to finely filter the coarse quantum dot ink described in S4 to remove undispersed quantum dot aggregates to obtain a quantum dot ink composite material.

[0115] Test Example 1: Performance Determination of Quantum Dot Ink Composite Materials

[0116] The detection method used in this test example is: using a surface tension tester to test the surface tension of the quantum dot ink composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 7. Reference standard: GB 11985-1989.

[0117] In this test example, the quantum dot particle size of the quantum dot ink composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 7 was measured using a dynamic light scattering (DLS) method.

[0118] The reference method was used to test the luminescence quantum yield of the quantum dot ink composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 7. The test results are shown in Table 1.

[0119] Table 1 Quantum dot ink composite material performance test results

[0120] Surface tension mN / m Quantum dot particle size ±0.5nm Luminescence quantum yield% Example 1 23 14.6 31.6 Example 2 25 17.1 28.1 Example 3 26 15.9 29.9 Comparative Example 1 57 28.2 21.8 Comparative Example 2 48 27.1 23.1 Comparative Example 3 54 25.6 22.6 Comparative Example 4 52 26.7 21.9 Comparative Example 5 30 28.1 19.9 Comparative Example 6 31 29.3 21.5 Comparative Example 7 29 26.7 22.6

[0121] It can be seen from the above results that the surface tension of Comparative Examples 1 to 4 is 50 to 57 mN / m, which is much larger than 23 to 26 mN / m of Examples 1 to 3. The larger surface tension is not conducive to the dispersion of the quantum dot material. It can also be seen from the fact that the quantum dot particle size of Comparative Examples 1 to 4 is 25.6 to 28.2 nm, which is larger than 14.6 to 17.1 nm of Examples 1 to 3, that the quantum dot material of Comparative Examples 1 to 4 has worse dispersibility, and some quantum dots aggregate, resulting in an increase in the quantum dot particle size. The aggregation of quantum dots is not conducive to the luminescence of the quantum dot material. It can be seen from the luminescence quantum yield that the luminescence quantum yield of Examples 1 to 3 is 29.9 to 31.6%, while the luminescence quantum yield of Comparative Examples 1 to 4 is only 21.8 to 23.1%. Therefore, the surfactant compound system used in the present invention has a good effect on improving the dispersibility of quantum dots. Compared with the nonionic / nonionic surfactant system used in Comparative Example 1, namely polyethylene glycol and dodecylamine polyoxyethylene ether, the nonionic / anionic surfactant system selected in the present invention, namely polyethylene glycol and epoxyethylene phosphate, can better reduce the surface tension of the ink system of the present invention and promote the dispersion of quantum dot materials. In the case of the same nonionic / anionic surfactant compound system, the preferred polyethylene glycol and epoxyethylene phosphate compound of the present invention has a better synergistic effect than the polyethylene glycol and sodium α-olefin sulfonate of Comparative Example 2, can better reduce surface tension, improve the dispersibility of quantum dots, and improve the luminescence quantum yield.

[0122] The surface tension of Comparative Examples 5 to 7 is 29 to 31 mN / m, slightly larger than that of Examples 1 to 3; the quantum dot particle size is 26.7 to 29.3 nm, larger than that of Examples 1 to 3; and the luminescence quantum yield is 19.9 to 22.6%, which is smaller than that of Examples 1 to 3. Analyzing the reason, the difference in luminescence quantum yield is also caused by the difference in quantum dot particle size. In Comparative Example 5, no dispersant water-based polyurethane is added, and its quantum dot dispersibility is reduced and the quantum dot particle size is increased. In addition, it can be seen from the table that the lack of water-based polyurethane increases the surface tension, so the water-based polyurethane and surfactant compound system has a synergistic effect, reduces surface tension, increases quantum dot dispersibility, and improves its luminescence yield. In summary, the preferred water-based polyurethane of the present invention can increase the dispersibility of quantum dots and increase their luminescence yield.

[0123] The difference between the data of Comparative Examples 6 and 7 and Examples 1 to 3 is caused by the viscosity modifier. The viscosity affects the dispersibility and stability of the dispersion system. The hydroxyethyl cellulose ether and high-boiling point kerosene used in the present invention promote the dispersion and stability of the quantum dots by reducing the surface tension of the quantum dot ink system.

[0124] In summary, the quantum dot ink composite material system used in the present invention can make the quantum dots have good dispersibility and better stability, the quantum dots are not easy to aggregate, and have better luminescence quantum yield.

Claims

1. A quantum dot ink composite material, characterized in that: The composition comprises the following components by weight: 3 to 5 parts of dispersant, 3 to 5 parts of quantum dot material, 30 to 50 parts of solvent, 0.3 to 0.5 parts of surfactant, 0.5 to 1 parts of viscosity modifier, 0.3 to 0.5 parts of drying agent, and 0.03 to 0.05 parts of defoaming agent; The surfactant is composed of a nonionic surfactant and an anionic surfactant in a mass ratio of 1:1-3.

2. The quantum dot ink composite material according to claim 1, characterized in that: The nonionic surfactant is selected from polyethylene glycol.

3. The quantum dot ink composite material according to claim 1, characterized in that: The anionic surfactant is selected from ethylene oxide phosphate esters.

4. The quantum dot ink composite material according to claim 1, characterized in that: The dispersant is waterborne polyurethane.

5. The quantum dot ink composite material according to claim 1, characterized in that: The viscosity modifier is a mixture of hydroxyethyl cellulose ether and high boiling point kerosene in a mass ratio of 1-3:1-2.

6. The quantum dot ink composite material according to claim 1, characterized in that: The quantum dot material is a perovskite quantum dot, the solvent is composed of water and epoxy resin in a mass ratio of 1:1 to 5, and the epoxy resin is a bisphenol A epoxy resin.

7. The quantum dot ink composite material according to claim 6, characterized in that: The quantum dot material is selected from one of CsPbBr3, FAPbBr3, CsPbI3 or CsPbCl3.

8. The quantum dot ink composite material according to claim 1, characterized in that: The drying agent is cobalt drying oil, and the defoaming agent is fatty alcohol ethoxysiloxane.

9. A method for preparing the quantum dot ink composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, dissolving the quantum dot material in a solvent and mixing them evenly to obtain a quantum dot solution; S2, mixing the quantum dot solution described in S1 with a dispersant, and mixing them evenly to form a quantum dot dispersion; S3, adding a surfactant to the quantum dot dispersion described in S2 and mixing evenly; S4, add viscosity regulator and drying agent, and mix well; S5. Perform fine filtration to obtain a quantum dot ink composite material.

10. The preparation method according to claim 9, characterized in that: The mixing methods in steps S1 to S4 are mechanical stirring or ultrasonic dispersion, and the duration is 30 to 40 minutes. The fine filtration in step S5 is performed using a 200-mesh sieve.

Citation Information

Patent Citations

  • Printing ink, quantum dot film, and quantum dot light-emitting diode

    CN111378323A

  • Ink, quantum dot film and quantum dot light-emitting diode

    CN113583512A